If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -1(-4))(3x + (-2)) = 3 + -1(5 + -3x)(2x + 3) Multiply -1 * -4 (2x + 4)(3x + (-2)) = 3 + -1(5 + -3x)(2x + 3) Reorder the terms: (4 + 2x)(3x + (-2)) = 3 + -1(5 + -3x)(2x + 3) (4 + 2x)(3x + -2) = 3 + -1(5 + -3x)(2x + 3) Reorder the terms: (4 + 2x)(-2 + 3x) = 3 + -1(5 + -3x)(2x + 3) Multiply (4 + 2x) * (-2 + 3x) (4(-2 + 3x) + 2x * (-2 + 3x)) = 3 + -1(5 + -3x)(2x + 3) ((-2 * 4 + 3x * 4) + 2x * (-2 + 3x)) = 3 + -1(5 + -3x)(2x + 3) ((-8 + 12x) + 2x * (-2 + 3x)) = 3 + -1(5 + -3x)(2x + 3) (-8 + 12x + (-2 * 2x + 3x * 2x)) = 3 + -1(5 + -3x)(2x + 3) (-8 + 12x + (-4x + 6x2)) = 3 + -1(5 + -3x)(2x + 3) Combine like terms: 12x + -4x = 8x (-8 + 8x + 6x2) = 3 + -1(5 + -3x)(2x + 3) Reorder the terms: -8 + 8x + 6x2 = 3 + -1(5 + -3x)(3 + 2x) Multiply (5 + -3x) * (3 + 2x) -8 + 8x + 6x2 = 3 + -1(5(3 + 2x) + -3x * (3 + 2x)) -8 + 8x + 6x2 = 3 + -1((3 * 5 + 2x * 5) + -3x * (3 + 2x)) -8 + 8x + 6x2 = 3 + -1((15 + 10x) + -3x * (3 + 2x)) -8 + 8x + 6x2 = 3 + -1(15 + 10x + (3 * -3x + 2x * -3x)) -8 + 8x + 6x2 = 3 + -1(15 + 10x + (-9x + -6x2)) Combine like terms: 10x + -9x = 1x -8 + 8x + 6x2 = 3 + -1(15 + 1x + -6x2) -8 + 8x + 6x2 = 3 + (15 * -1 + 1x * -1 + -6x2 * -1) -8 + 8x + 6x2 = 3 + (-15 + -1x + 6x2) Combine like terms: 3 + -15 = -12 -8 + 8x + 6x2 = -12 + -1x + 6x2 Add '-6x2' to each side of the equation. -8 + 8x + 6x2 + -6x2 = -12 + -1x + 6x2 + -6x2 Combine like terms: 6x2 + -6x2 = 0 -8 + 8x + 0 = -12 + -1x + 6x2 + -6x2 -8 + 8x = -12 + -1x + 6x2 + -6x2 Combine like terms: 6x2 + -6x2 = 0 -8 + 8x = -12 + -1x + 0 -8 + 8x = -12 + -1x Solving -8 + 8x = -12 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -8 + 8x + x = -12 + -1x + x Combine like terms: 8x + x = 9x -8 + 9x = -12 + -1x + x Combine like terms: -1x + x = 0 -8 + 9x = -12 + 0 -8 + 9x = -12 Add '8' to each side of the equation. -8 + 8 + 9x = -12 + 8 Combine like terms: -8 + 8 = 0 0 + 9x = -12 + 8 9x = -12 + 8 Combine like terms: -12 + 8 = -4 9x = -4 Divide each side by '9'. x = -0.4444444444 Simplifying x = -0.4444444444
| =h(a+b) | | -7-6=x | | 10x-11x+3=0 | | -9-3=x | | n-9=-42 | | -5(6m-3)=38-7m | | -10+4x=-42 | | 0.88=log(x) | | 2(9x+631)=2x+270 | | .88=log(x) | | 1-5b-4b=10 | | 11z=-100 | | 3n-9+3=24 | | 3(14-4y)-5y=-9 | | 6y+5=10y-1 | | 12k+14=10k-2k-7 | | -3(x+4)+16= | | J-8=-5 | | 10x-8=31.5 | | 2(2x-11)=2x | | 8x-4+8x-4+21+3=180 | | 9x^2-42x+37=0 | | 11-3(x+4)+5= | | H-41=13 | | 24=3(x)-6 | | (10x+36y)+(2x+y)= | | 63=60.50p+17.50 | | 8x-4+8x-4+4+3=180 | | 9=3(x)-6 | | 152+8h= | | 19=b-3 | | -3=3(x)-6 |